(untitled) (The Pakistan Development Review, 1994)
This paper analyses the impact of internal migration on earnings within the human capital model framework. Since migrants constitute a non-random sample of population, the endogenous nature of migration decision warrants necessary correction for the selectivity bias in their eamings function. The Mincer-type eamings model is thus augmented to determine the extent of this bias. Besides estimating the standard Mincerian eamings model, the paper also attempts to verify the leam-as-you-go proposition by introducing migration duration variables in the eamings model. Based on the household level Population, Labour Force, and Migration (1979- 80) survey data, the analysis yields the following important conclusions: (i) the data allowed a meaningful estimation of Mincerian earnings function for migrants and non-migrants; (ii) the level of schooling was one of the important determinants of the distribution of income both for migrants and non-migrants-the four categorical variables of education were in general statistically significant with expected signs, implying that the hypothesis of a positive relationship between income and education was accepted; (iii) the rates of return to education improved systematically with higher levels of education, thus confirming the notion that education serves as a signalling device; (iv) the age-income profile was almost linear for migrants but showed concavity for non-migrants; (v) the presence of sample-selection was observed for migrants; and (vi) even after controlling for the influence of personal characteristics, i.e., education and experience, the long-standing migrants eamed relatively more at the destination than the more recent migrants.